Remoção de contaminantes emergentes via sistema eletroquímico fotoassistido - Feitosa, Maria Helena Alves (2020)
The present work presents the characterization and application studies of semiconductor materials used in the degradation of naproxen in environmental pathways. It is recognized that semiconductor materials present as fundamental supports in the technological development for methods of wastewater treatment, in order to eliminate compounds that may contribute to the disruption of the reproductive system of environmental species. In this scenario, the photoanodes were produced based on titanium dioxide (TiO2) film over a glass surface conductive with tin oxide dopped with fluorine (FTO). Then, cadmium sulfide nanoparticles (CdS) were deposited on the FTO/TiO2 systems using an electrodeposition technique. The time and temperature of the deposition were studied and optimized to verify the best proportion and thickness of the CdS film. These studies lead to increase in the photocurrent effect. In this work, the films were characterized by linear sweep voltammetry, chronoamperometry, transmission electron microscopy, dispersive energy diffraction of the selected area, X-ray diffraction and diffuse reflectance. All these techniques were performed to evaluate the morphological, structural, and optical properties of the proposed films. The degradation process of samples containing naproxen was characterized by UV-vis spectroscopy and determination of total organic carbon. From the characterizations, it was observed that the TiO2 film is composed of spherical particles distributed in agglomerates, whose major phase is pure anatase. The CdS particles presented as a polycrystalline material, with low energy between bands, leading to an increase in the catalytic sites, which led to an increase in the photo-anode photo response. The photoanodes were applied to standardized environmental samples. For each conditions, the rate constant in the decay of the drug concentration was estimated, using as standard a sample that contained a 1.0 x 10-5 mol L-1 solution of naproxen, in pH phosphate buffer medium 7.0. The photoanodes were used in the photo-electro degradation processes under UVc radiation, with application of + 2.0 V for 6 hours. As expected, the FTO/TiO2/CdS electrode showed a superior response to TiO2 with kinetic constant estimated at k = 1.1 x 10-2 min-1 and t1/2 of 62.16 min-1. The organic carbon study revealed a decrease of 22.1 % of the degradation process. Finally, the estimated energy consumption involved (17,2 kWh kg-1) in terms of costs would be, in 2020, equivalent to US$ 2.68 to remove 1.0 kg of naproxen in aqueous waste.